WAWASAN AL-QUR’AN TENTANG INFÂQ - Achyar Zein (State Islamic University North Sumatra, 2008)
Abstract: The Qur’anic Perspectives on Donation (Infâq). Wealthdistribution is an important concept regarding social welfare. One of key concepts on wealth distribution in the Qur’an is infâq, which stands for efficient attitude and practices on one hand and reducing wastefullness on the other. Works on Qur’anic exegesis and Islamic law, both classical works and modern ones, contain much discussion about this concept. The author argues that one of the most dominant views regarding infâq is that it is considered as a non-binding act of charity or a recommended act (sunnah) in Islamic law. Ibn ‘Abbâs, for instance, holds that it renders a bridging concept between zakât and almsgiving. This paper is an attempt to explore the concept of infâq by analyzing various Qur’anic verses and provide a comparison with prominent views of Islamic scholars.Kata Kunci: infâq, keborosan dan al-nafaqah